Morphological characterization and genetic divergence among melon accessions - Silva, Jordana Antônia dos Santos; Silva, Suzanny Maria de Andrade Oliveira; Freitas, Nardiele de Souza Souto; Veloso, Maria Beatriz de Lima; Valadares, Ricardo de Normandes; Oliveira, Frederico Inácio Costa de (Revista Ceres, 2025)
Melon, a member of the Cucurbitaceae family, is cultivated in over 100 countries and is a crop of great global importance. The significant morphological variability, encompassing attributes such as size, shape, color, and texture of the rind and flesh, alongside aroma and flavor, indicates the extensive phenotypic diversity the crop manifests. This diversity represents a crucial resource for breeding programs aimed at the species’ improvement. Such variation enables breeders to select superior individuals for subsequent crosses, to develop cultivars adapted to diverse environmental and management conditions. The objective of this study was to estimate the genetic divergence between melon accessions for morphological traits. Twenty-four accessions and one commercial cultivar were evaluated. The generalized Mahalanobis distance was used as a measure of dissimilarity. Then, the clustering analysis of the accessions was performed using the Tocher optimization method and the hierarchical agglomerative clustering method (UPGMA). Both the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) hierarchical method and the Tocher optimization agglomerative method yielded the formation of three distinct groups, exhibiting a congruence of 96% between them. It was found that the longitudinal diameter, transverse diameter, and length-width/fruit ratio were the characteristics that presented the highest percentage of contribution to divergence between the accessions evaluated.